Describing Music Materials: A Manual for Resource Description of Printed and Recorded Music and Music Videos, 4th ed. – by Richard P. Smiraglia with Jihee Beak (Book Review) - Boyd, Alastair (CAML Review / Revue de l’ACBM, 2017)
[no abstract]